Penerapan Model Pembelajaran GOLD untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 4 Pangkajene - Misbahuddin Darwis; Zaid Zainal; Kamaruddin Hasan (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The problem in this research is low learning outcomes in mathematics for class V students based on results of observations. This research aims to application of the GOLD learning model to improve the mathematics learning process in data presentation material for class V students SDN 4 Pangkajene and determine in mathematics learning outcomes by applying the GOLD learning model. The approach is a qualitative approach where the results obtained are described with the type of classroom action research. The research results in the first cycle of teacher activity classified sufficient (C), student activity classified as sufficient (C) and student learning outcomes classified as sufficient (C). In cycle II teacher activities are classified sufficient (C), student activities are classified as sufficient (C) and the student learning outcomes is classified as sufficient (C). In cycle III, by correcting existing deficiencies, where teacher activity is classified as good (B), student activity is classified as good (B) and student learning outcomes is classified good (B). The conclusion of the research is that applying the GOLD learning model can improve the process and results of mathematics learning in data presentation material for class V students UPT SDN 4 Pangkajene Sidrap Regency.